Capital markets, derivatives, and the law : positivity and preparation - Rechtschaffen, Alan N. (New York, NY : Oxford University Press, 2019)
The American economy looks good. This is in the wake of a decade where dramatic failures in individual markets and institutions sparked a global financial crisis resulting in political, social and economic unrest. In the United States, a host of legislative acts completely reshaped the regulatory landscape. This book investigates the structure and the workings of financial instruments and the capital markets.
Previous edition issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2019).
Keywords: Financial instruments -- United States; Derivative securities -- Law and legislation -- United States; Capital market -- Law and legislation -- United States; Securities industry -- Law and legislation -- United States; Law; Laws of specific jurisdictions & specific areas of law